Assessment of some characteristics and properties of α-mangostin loaded by carrageenan/chitosan particles - Thuy Chinh , Nguyen; Nguyen Thi Hien,; Nguyen Thi Minh Tu,; Hoang Dinh Hoa,; Tran Dinh Thang,; Hoang Phuong Thao,; Thai Hoang, (Vietnam Journal of Science and Technology, 2022)
α-mangostin - an active compound extracted from mangosteen fruit peels – has been known with high anti-oxidation, antimicrobial, anti-inflammatory, antiphrastic, antiviral etc. One of disadvantages of α-mangostin is poorly soluble in aqueous solution. Loading α-mangostin by some biopolymers could improve the solubility of α-mangostin in aqueous. Therefore, this paper presents the preparation and characterization of carrageenan/chitosan particles loading α-mangostin - an active compound extracted from mangosteen fruit peels. The carrageenan/chitosan/α-mangostin particles were prepared by ionic gelation method in the presence of sodium tripolyphosphate as a cross-linking agent and potassium chloride as a gel agent. The functional groups in the particles were characterized by infrared spectroscopy. The hydrophobic/hydrophilic characteristic of the particles were assessed through the determination of contact angle of water droplet on the surface of the particles. The drug loading efficacy and solubility of carrageenan/chitosan/α-mangostin particles in buffer/ethanol solutions were also evaluated and discussed. The obtained results suggest that α-mangostin has been loaded by carrageenan/chitosan blend and the content of α-mangostin had a negligible effect on the vibrations of functional groups in the carrageenan/chitosan/α-mangostin particles. As increasing α-mangostin content in the particles, the contact angle of the particles decreased, corresponding to the increase in their hydrophilic ability. The α-mangostin loading efficacy of the particles was quite high, > 90 %. The assessment of the solubility of the particles in ethanol/buffer solutions shows that the solubility of the particles was better than that of α-mangostin.